Sandwich-structured Au@polyallylamine@Pd nanostructures: tuning the electronic properties of the Pd shell for electrocatalysis. Issue 31 (18th July 2016) - Li, Fu-Min; Kang, Yong-Qiang; Peng, Rui-Li; Li, Shu-Ni; Xia, Bao-Yu; Liu, Zong-Huai; Chen, Yu
Abstract : We report herein the synthesis of core–shell sandwich Au@polyallylamine@Pd nanostructures, in which the electronic structure of the Pd shell can be strongly tuned by the medial polyallylamine layers. Abstract : We report herein the synthesis of core–shell sandwich Au@polyallylamine@Pd nanostructures, in which the electronic structure of the Pd shell can be strongly tuned by the medial polyallylamine layers. The designed Au@polyallylamine@Pd nanostructures exhibit significantly improved electrocatalytic activity and stability for the formic acid oxidation reaction through the preferential dehydrogenation pathway.